2011
DOI: 10.5581/1516-8484.20110126
|View full text |Cite
|
Sign up to set email alerts
|

Acute promyelocytic leukemia presenting as an extradural mass

Abstract: Acute promyelocytic leukemia is potentially a highly curable type of leukemia that usually presents with pancytopenia, coagulopathies and bleeding. We describe a case of an unusual presentation of acute promyelocytic leukemia. A 53 year-old male was admitted complaining of pain and weakness in his legs. He presented at examination a spastic paraparesis with a sensitive level at the eighth thoracic medullar (T8) segment. Magnetic resonance imaging showed a posterolateral extradural mass from T6 through T8 segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Four of five patients were treated with radiotherapy; no significant radiotherapy effects were found. Radiotherapy alone seemed to be ineffective in some cases (18,19,21,22,24). One retrospective study demonstrated that majority of patients that presented with MS had not received radiotherapy because the mass regressed after induction chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Four of five patients were treated with radiotherapy; no significant radiotherapy effects were found. Radiotherapy alone seemed to be ineffective in some cases (18,19,21,22,24). One retrospective study demonstrated that majority of patients that presented with MS had not received radiotherapy because the mass regressed after induction chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Nine cases have been reported from 2005 to 2015 [3][4][5][6][7][8][9][10][11] (Table 1). It often appears like a solid tumour known as granulocytic sarcoma or myeloid, or also chloroma as seen in our patient [12].…”
Section: Discussionmentioning
confidence: 99%
“…2 had epidural or spinal masses at the time of diagnosis of APL [8,9] ; and 2 had a thoracic spinal [10] or paraspinal [11] mass as the only evidence of relapsed APL. These patients were treated with combinations of surgery, radiotherapy, and chemotherapy, including ATRA, and achieved complete responses for variable periods of time.…”
Section: Discussionmentioning
confidence: 99%